Asian Infrastructure Investment Bank as an instrument for Chinese influence? Supplementary versus remedial multilateralism. (September 2021) - Kaya, Ayse; Kilby, Christopher; Kay, Jonathan
Highlights: Contrary to past conjectures, we do not find that countries close to China have better access to AIIB loans. Instead, countries economically distant from China have better access. This is consistent with remedial multilateralism. Remedial multilateral allows the dominant member to strengthen weak bilateral ties and expand its sphere of influence. Findings contrast with studies of American influence and reflect the unique circumstances facing China and the AIIB. Abstract: Starting even before its founding in 2015, the Asian Infrastructure Investment Bank (AIIB) has attracted controversy. Critics—especially the U.S. administration—claim the bank is an instrument of China intended to advance narrow Chinese interests and thereby undermine U.S. influence globally. But does AIIB lending show any Chinese influence? Analysis on AIIB lending patterns has been scant. Based on AIIB loan data through the end of 2019, our analysis suggests the AIIB is facilitating "remedial multilateralism" for China, whereby countries economically distant from China have privileged access to AIIB loans. This is contrary to expectations from "supplementary multilateralism, " whereby the multilateral setting reinforces existing bilateral ties. The paper advances the notions of supplementary and remedial multilateralism and provides a comprehensive analysis of AIIB loans in the first four years of the institution's operation. It, thus, contributes to the understanding of how China's rise is affecting the landscape of multilateral development finance.